The Role of Inquiry Based Learning to Improve Reading Comprehension of EFL Students - ' Ermawati (ELS Journal on Interdisciplinary Studies in Humanities, 2018)
Approaches in reading have widely emerged to fulfill the needs of learners to comprehend a text and to change their reading habit which is one of them is Inquiry Based Learning (IBL). Thus, this study aims to identify the role of Inquiry Based Learning to improve reading comprehension. The design of this study was mixed method with QUAN-qual model. The quantitative method used quasi-experimental design with control and experimental group including pre-test and post-test. It used purposive sampling technique to determine the samples who involved 40 students; 19 students in control class and 21 students in experimental class. This study was conducted at third semester students of English Education Department of STKIP Muhammadiyah Sidrap. The data were gained through test and non-test (questionnaire and interview). Then, the data were analyzed through SPSS 22. The significant findings of the recent study was the roles of IBL; developing students’ reading proficiency, engaging the students with complex texts, practicing students’ all levels of comprehension as they take a part in IBL phases,activating students prior knowledge, aligning inquiry process to students’ reading comprehension, providing students to work with team and enhancing students’ learning process. Finally, this study could be implemented practically and pedagogically in the study of IBL.